Transparent glass ceramic and preparation method thereof

By adjusting the component ratio of transparent glass ceramics to form them in one heat treatment, the high cost problem caused by two-stage heat treatment in the prior art is solved, and a more efficient preparation process and lower usage cost is achieved.

CN119638189APending Publication Date: 2025-03-18深圳市昊迦科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411992980.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing transparent glass ceramics require two-stage heat treatment during the preparation process, resulting in high energy and time costs.

Method used

By adjusting the proportion of each component, the temperature intervals of nucleation and crystallization are intersected, and glass ceramics can be formed by only one heat treatment. The specific component ratios are: SiO2: 36.0-45.0%, Al2O3: 23.0-32.5%, Na2O: 15.0-22.5%, K2O: 0-1.0%, Li2O: 0.5-5.5%, B2O3: 1.5-8.0%, ZrO2: 1.5-5.5%, TiO2: 0-1.0%, P2O5: 1.0-6.5%, MgO: 0-2.0%, SnO2: 0.1-0.5%, and meets the specific component ratio relationship.

Benefits of technology

It has achieved the reduction of the use of lithium carbonate, reduced energy and time costs, simplified the preparation process, and improved the application efficiency of glass ceramics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638189A_ABST
    Figure CN119638189A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic glass, and discloses transparent glass ceramic and a preparation method thereof. The invention discloses a high-temperature-resistant ceramic which is prepared from the following components in percentage by mass: 36.0 to 45.0 percent of SiO2, 23.0 to 32.5 percent of Al2O3, 15.0 to 22.5 percent of Na2O, 0 to 1.0 percent of K2O, 0.5 to 5.5 percent of Li2O, 1.5 to 8.0 percent of B2O3, 1.5 to 5.5 percent of ZrO2, 0 to 1.0 percent of TiO2, 1.0 to 6.5 percent of P2O5, 0 to 2.0 percent of MgO and 0.1 to 0.5 percent of SnO2. According to the invention, the sodium element is one of the main elements of the crystalline phase, which is different from at least two-stage heat treatment of nucleation-crystallization on the basic glass in the traditional transparent glass ceramic, and the glass ceramic can be formed by only carrying out one-time heat treatment on the basic glass, so that the energy and time cost can be saved, and the use cost can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of glass ceramics, and in particular to a transparent glass ceramic and a preparation method thereof. Background Art

[0002] During the use of consumer electronic products (such as watches, tablets, mobile phones, notebooks and cameras, etc.) and vehicle-mounted display devices, the display screens are easily damaged, deformed and scratched due to passive or active collisions with hard surfaces. Therefore, the protective glass must be high-strength and scratch-resistant, while having excellent optical properties, so as to reduce the breakage rate during the use of the equipment and extend its service life.

[0003] The main crystal form of the currently popular transparent glass ceramics is the LAS system with lithium Li as the main element, which requires a large amount of lithium-containing compounds. However, as an important component of the recent new energy storage materials, the cost of lithium-containing compounds is high, such as lithium carbonate.

[0004] At the same time, in the process of microcrystallization heat treatment of basic glass, at least two-stage heat treatment of "nucleation-crystallization" is usually adopted, which consumes a lot of energy and time costs.

[0005] Therefore, the prior art needs to be further improved and enhanced. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the present invention aims to provide a transparent glass ceramic, which aims to solve the problem that the transparent glass ceramic of the existing LAS system needs to undergo two-stage heat treatment during the preparation process, which consumes a lot of energy and time costs.

[0007] The above object of the present invention is achieved by the following technical solution: a transparent glass ceramic, wherein the components, in terms of mass percentage, include:

[0008] SiO2: 36.0~45.0%,

[0009] Al2O3: 23.0~32.5%,

[0010] Na2O: 15.0~22.5%, K2O: 0~1.0%, Li2O: 0.5~5.5%,

[0011] B2O3: 1.5~8.0%,

[0012] ZrO2: 1.5~5.5%, TiO2: 0~1.0%, P2O5: 1.0~6.5%,

[0013] MgO: 0~2.0%, SnO2: 0.1~0.5%;

[0014] The components also satisfy at least one of the following relationships:

[0015] 0.98≤(Al2O3%+Na2O%) / SiO2%≤1.36;

[0016] 18%≤(Na2O+Li2O+K2O)%≤24.50%;

[0017] 3.0%≤(ZrO2+TiO2+P2O5)%≤9.0%;

[0018] 2.80%≤(B2O3+MgO)%≤8.0%.

[0019] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0020] As a preferred technical solution, the transparent glass-ceramic, wherein the transparent glass-ceramic also contains 0.1 to 0.80 wt % of a clarifier, the clarifier being selected from one or more of NaCl, Sb2O3, As2O3, nitrates, and sulfates; the sum of the percentages of the components of the transparent glass-ceramic containing the clarifier is 100%.

[0021] As a preferred technical solution, the transparent glass-ceramics, wherein the main crystalline phase of the transparent glass-ceramics is sodium nepheline crystalline phase and / or triclinic nepheline crystalline phase, and the secondary crystalline phase is one or more of sodium silicate crystalline phase, β-quartz solid solution crystalline phase and zirconium oxide crystalline phase.

[0022] As a preferred technical solution, in the transparent glass-ceramic, the proportion of the secondary crystalline phase to all crystalline phases is ≤10%, the average grain size is 20-70 nm, and the crystallinity is 20%-70%.

[0023] In a second aspect, a method for preparing the transparent glass-ceramic according to the first aspect, comprising:

[0024] Provide basic glass;

[0025] Heat treating the base glass to obtain the transparent glass ceramic, wherein the heat treatment temperature is 570° C. to 680° C. and the heat treatment time is 15 to 120 min;

[0026] The base glass comprises SiO2: 36.0-45.0wt%, Al2O3: 23.0-32.5wt%, Na2O: 15.0-22.5wt%, K2O: 0-1.0wt%, Li2O: 0.5-5.5wt%, B2O3: 1.5-8.0wt%, ZrO2: 1.5-5.5wt%, TiO2: 0-1.0wt%, P2O5: 1.0-6.5wt% , MgO: 0~2.0wt%, SnO2: 0.1~0.5wt%; the components also satisfy at least one of the following: 0.98≤(Al2O3%+Na2O%) / SiO2%≤1.36; 18%≤(Na2O+Li2O+K2O)%≤24.50%; 3.0%≤(ZrO2+TiO2+P2O5)%≤9.0%; 2.80%≤(B2O3+MgO)%≤8.0%.

[0027] As a preferred technical solution, the preparation method of the transparent glass-ceramic, wherein the preparation method also includes: immersing the transparent ceramic glass in a molten salt to obtain a strengthened transparent glass-ceramic; the molten salt temperature is T, 400℃≤T≤480℃; the molten salt is NaNO3 and / or KNO3 in a molten state.

[0028] As a preferred technical solution, the preparation method of the transparent glass-ceramic is as follows, wherein the depth of the surface stress layer of the strengthened transparent glass-ceramic is DOL, 105 μm≤DOL≤155 μm, and the surface compressive stress CS≥650 MPa.

[0029] As an optimal technical solution, the preparation method of the transparent glass-ceramic is described, wherein the Vickers hardness of the surface of the strengthened transparent glass-ceramic is ≥6.5Gpa; when the thickness is less than 0.70mm and the light wavelength is 400nm~780nm, the average transmittance of the chemically strengthened glass-ceramic product is ≥89%, the color control LAB value is 0.60≤|B|≤1.0, and the haze Haze≤0.18%.

[0030] As a preferred technical solution, the preparation method of the transparent glass-ceramic is as follows: the strengthened transparent glass-ceramic withstands a height of ≥190cm and an impact energy of ≥0.35 joules under the condition of 120-mesh sandpaper and a 200g counterweight.

[0031] In a third aspect, the transparent glass-ceramic described above or the transparent glass-ceramic prepared by the preparation method described above is used as a material for preparing screen protection covers of consumer electronic products and vehicle-mounted display devices.

[0032] Beneficial effects: Compared with the prior art, the present invention uses Na as one of the main elements of the crystal phase, which is different from the LAS system glass ceramics on the market that use Li as the main element of the crystal phase, and reduces the amount of lithium carbonate used. At the same time, the present invention is different from the traditional transparent glass ceramics that use at least two-stage heat treatment of the "nucleation-crystallization" process for the microcrystallization of the basic glass. The present invention adjusts the proportion of each component so that the temperature range of nucleation and the temperature range of crystallization overlap, so that the basic glass only needs to be heat treated once to form glass ceramics, which can greatly save energy and time costs, reduce the cost of use, and greatly improve the application of glass ceramics. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is the XRD spectrum of Example 1 of the present invention;

[0034] Figure 2 It is the phase diagram of Na2O-Al2O3-SiO2 system of the present invention;

[0035] Figure 3 It is the transmittance of the chemically strengthened glass ceramic of Example 1 of the present invention. DETAILED DESCRIPTION

[0036] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0037] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0039] Unless otherwise specifically stated, the relative arrangement of the parts and steps described in these embodiments, the numerical expressions and numerical values ​​do not limit the scope of the present invention. At the same time, it should be clear that, for ease of description, the sizes of the various parts shown in the drawings are not drawn according to the actual proportional relationship. The technology, methods and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but in appropriate cases, the technology, methods and equipment should be regarded as part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar numbers and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further discussed in subsequent drawings.

[0040] In order to better understand the content of the present invention, some terms in the present invention are explained:

[0041] Basic glass: Glass that has not been nucleated, crystallized or chemically strengthened by ion exchange is prepared by uniformly mixing compounds containing various oxides (including silicon dioxide, aluminum oxide, sodium oxide, calcium oxide, etc.), melting them at high temperature, and then forming them by one of the following methods: float process, overflow down-draw process, roller pressing process or casting process.

[0042] Glass ceramics: also known as microcrystalline glass, is a type of solid composite material that contains both glass phase and crystal phase (microcrystalline phase, crystalline phase) and is prepared by subjecting base glass to a targeted controlled crystallization treatment.

[0043] Nucleation: The base glass is heat treated to make the nucleating material in the glass grow tiny crystal nuclei.

[0044] Crystallization: The base glass is grown into a certain crystal based on the crystal nucleus through heat treatment.

[0045] Crystalline phase: It is the microscopic structure of crystals, and is a general term for a large number of crystalline solid phases. The main crystal phase is the crystal phase that accounts for a relatively large proportion (such as more than 45%) in the crystal phase, and the secondary crystal phase is the crystal phase that accounts for a relatively small proportion (such as less than 20%) in the crystal phase.

[0046] Crystallinity: It is used to indicate the proportion of the crystalline region in (chemically strengthened) glass-ceramics, generally based on the volume ratio of the crystalline phase in the entire glass-ceramics.

[0047] The transparent glass ceramic provided by the present invention comprises, by mass percentage, the following components: SiO2: 36.0-45.0%, Al2O3: 23.0-32.5%, Na2O: 15.0-22.5%, K2O: 0-1.0%, Li2O: 0.5-5.5%, B2O3: 1.5-8.0%, ZrO2: 1.5-5.5%, TiO2: 0-1.0%, P2O5: 1.0-6.5 %, MgO: 0~2.0%, SnO2: 0.1~0.5%; the components also satisfy at least one of the following relationships: 0.98≤(Al2O3%+Na2O%) / SiO2%≤1.36; 18%≤(Na2O+Li2O+K2O)%≤24.50%; 3.0%≤(ZrO2+TiO2+P2O5)%≤9.0%; 2.80%≤(B2O3+MgO)%≤8.0%.

[0048] In the present invention, SiO2, Al2O3 and Na2O are the main results of forming the crystal forms of sodium pyroxene, triclinic pyroxene, sodium silicate, β-quartz solid solution, etc. in the present invention. The proportion of the three components meets certain conditions to form glass ceramics with sodium pyroxene and triclinic pyroxene as the main crystal forms. The three components have different functions, specifically:

[0049] SiO2 is one of the main components of the network oxide of basic glass and glass ceramic materials, and is one of the important components that constitute the Si-O tetrahedron in the main body and form the network structure. Based on the present invention, the mass fraction of SiO2 is 36.0-45.0wt%, preferably 38-45wt%, for example, it can be 36.0wt%, 37.0wt%, 38.0wt%, 39.0wt%, 40.0wt%, 41.0wt%, 42.0wt%, 43.0wt%, 44.0wt%, and 45.0wt%, and any component in the range formed by any two of the above values. When the SiO2 content is too low, the product made of the material has poor resistance to devitrification, poor scratch resistance and low hardness. When the SiO2 content is greater than 45.0wt%, it is difficult to control the composition and size of the precipitated crystals after heat treatment;

[0050] Al2O3 is one of the main components of the internal network structure of basic glass and glass-ceramic materials, and is also the main component of the crystal forms such as sodium pyroxene and triclinic pyroxene, which can significantly improve the thermal stability and ion exchange performance, and is helpful to generate the target crystal. Based on the material to which the present invention relates, the mass fraction of Al2O3 is Al2O3 (23.0~32.5wt%), preferably 23.0~30.0wt%, for example, 23.0wt%, 24.0wt%, 25.0wt%, 26.0wt%, 27.0wt%, 28.0wt%, 29.0wt%, 30.0wt%, 31.0wt%, 32.0wt%, 32.50wt% and any two of the above-mentioned numerical components can be selected to constitute any numerical value in the composition range. But when Al2O3 content exceeds 32.5wt%, it is easy to cause the transmittance to decrease and the high temperature viscosity to increase, and the melting point increases, which is unfavorable for production.

[0051] Na2O is one of the main components of sodium nepheline, triclinic nepheline and other crystal forms, and is also an important element involved in ion exchange in the chemical strengthening process of glass ceramics. At the same time, Na2O is a flux when the base glass is melted at high temperature, which can significantly reduce the melting temperature of the base glass. The material involved in the present invention has a mass fraction range of Na2O of 15.0 to 22.5wt%, preferably 15.0 to 22.0wt%, specifically 15.0wt%, 16.0wt%, 17.0wt%, 18.0wt%, 19.0wt%, 20.0wt%, 21.0wt%, 22.0wt%, 22.50wt%, and a value in one of the above two composition ranges.

[0052] At the same time, Na2O, K2O and Li2O, as alkali metal elements, are effective in reducing the viscosity of the glass during the melting of the base glass. In particular, the Al2O3 content in the present invention is much higher than that in the LAS system glass ceramics. Therefore, the proportion of the three alkali metal element oxides also needs to meet certain conditions. Among the three alkali metals:

[0053] K2O is often added to reduce the high temperature viscosity of the base glass, significantly improve the formability and fluidity of the base glass at high temperature, and significantly reduce the incidence of cracks. A small amount of K2O added can slow down the crystallization behavior that occurs when the glass is formed. The material involved in the present invention has a K2O content range of 0.0-1.0wt%, preferably 0.0-0.50wt%, and specifically in the present invention can be 0.0wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt% and any value in the range of any two of the above values.

[0054] Li2O is an oxide with high alkali metal activity and is an external oxide of the glass network. As one of the additives to reduce the high temperature viscosity of the base glass, it significantly improves the high temperature fluidity of the base glass. + In the glass-ceramic material of the components described in the present invention, ion exchange chemical strengthening reaction can be involved to further enhance the mechanical properties of the glass-ceramic. The glass-ceramic material involved in the present invention has a Li2O content range of 0.5-5.5wt%, preferably 1.0-4.5wt%. In the present invention, it can specifically be 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%, 5.5wt%, and any value in the range composed of any two of the above values.

[0055] B2O3 and MgO are the external oxides of the glass network. Maintaining a specific ratio between the two can effectively ensure the chemical stability of the basic glass and glass ceramics. Among them:

[0056] A certain amount of B2O3 can control the linear thermal expansion coefficient of the base glass and glass ceramics, while maintaining the chemical durability and mechanical strength of the ceramicized body glass ceramics. The glass ceramic material involved in the present invention has a B2O3 content range of 1.5-8.0%wt, preferably 2.0-7.0%wt, and specifically can be 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt%, 7.0wt%, 7.5wt%, 8.0wt% and any value in the range of any two of the above values. Too high or too low B2O3 content is unstable in chemical resistance of the glass ceramic material formed after the base glass nucleation and crystallization.

[0057] MgO, as a divalent alkaline earth metal, can effectively break the bridging oxygen bond of Si-O tetrahedron inside the base glass. 2+ It is beneficial to promote the glass to have a lower refractive index and density in the tetrahedron. The MgO content in the present invention ranges from 0 to 2.0wt%, specifically 0wt%, 0.50wt%, 1.50wt%, 2.0wt%, and any value in the range formed by any two of the above values.

[0058] ZrO2, TiO2 and P2O5 are three oxides that are usually used as important nucleating agents for crystals in glass ceramics. The proportion of the three together can significantly affect the growth of crystals in glass ceramics, but due to their different roles, there are significant differences:

[0059] In the basic glass and glass ceramics described in this article, it is found that ZrO2 can improve the stability of the glass by significantly reducing the devitrification of the glass and lowering the liquidus temperature during the formation process. At high temperatures, ZrSiO4 can form a main liquidus phase, which significantly reduces the liquidus viscosity. At the same time, the tetragonal crystal form of ZrO2 can increase the strength and toughness of glass ceramics; the content range of ZrO2 in the present invention is 1.5-5.5wt%, specifically 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%, 5.5wt% and any value in the range composed of any two of the above values.

[0060] TiO2 is the most abundant element in the base glass and glass-ceramics described in this article. 4+ The body-centered octahedral structural unit, and 6 O 2- Coordinated in six directions, containing 1 Ti 4+ The oxygen octahedron can effectively promote the growth of crystal nuclei in the base glass during the nucleation crystallization heat treatment process, and at the same time improve the stability of the glass; the introduction of TiO2 effectively promotes the precipitation of crystal nuclei in the nucleation process, and at the same time, the introduction of TiO2 easily causes phase separation in the base glass, resulting in crystallization, affecting the formation of the glass. Too high a proportion of TiO2 will also cause the color of the base glass to deepen. The content range of TiO2 in the present invention is 0-1.0wt%, specifically 0%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt% and any value in the range composed of any two of the above values.

[0061] P2O5 can be used as a nucleating agent in base glass and glass ceramics to form bulk nucleation, which can promote the phase separation and overall crystallization ability of base glass, and can also form sodium phosphate crystals. If the P2O5 concentration is too low, the base glass is not easy to crystallize during heat treatment, and only forms crystals from the surface to the inside at a higher temperature and low viscosity. If the P2O5 concentration is too high, it will be difficult to control and easy to devitrify when cooling during the formation process of the base glass. The P2O5 content range of the present invention is 1.0-6.5wt%, specifically 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt% and any value in the range composed of any two of the above values.

[0062] SnO2 is an effective clarifier for base glass. Its introduction is beneficial to reducing the formation of gas defects in the glass melt, reducing the number of bubbles in the melt, and improving the clarification effect. The content range of SnO2 in the present invention is 0.1-0.5wt%, specifically 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt% and any value in the range composed of any two of the above values.

[0063] It also contains 0.1-0.80wt% of other clarifiers, including at least one of NaCl, Sb2O3, As2O3, nitrates, and sulfates; the clarifier can homogenize the oxides of the base glass in a molten state and evenly distribute the oxides in the glass body. The content range of the clarifier in the present invention is 0.1-0.80wt%, specifically 0.1wt%, 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt% and any value in the range composed of any two of the above values.

[0064] Based on the same inventive concept, the present invention also provides a method for preparing transparent glass ceramics, including the preparation of basic glass, the preparation of glass ceramics, the preparation of reinforced glass ceramics and other operational process flows.

[0065] The details are as follows:

[0066] S1. Preparation of basic glass: uniformly mixing, melting, clarifying, molding and annealing the compounds corresponding to the above oxides to obtain basic glass, wherein the molding method of the basic glass is one of float method, overflow method, roller pressing or continuous melting casting method;

[0067] S2, glass ceramic preparation: heat-treating the base glass obtained in step S1 to obtain glass ceramic containing the crystalline phase, wherein the heat-treating temperature is 570° C. to 680° C. and the heat-treating time is 15 to 120 min;

[0068] S3, preparation of chemically strengthened glass ceramics: placing the glass ceramics obtained in step S2 in a molten state of NaNO3, KNO3 or a mixed molten salt of the two at a temperature of 400°C≤T≤480°C and soaking for 2 to 12 hours to obtain chemically strengthened glass ceramics;

[0069] For some production examples, the base glass used for preparation can be prepared by a roll pressing method, a continuous melting casting method, a float method or an overflow method.

[0070] Based on the same inventive concept, the present invention also provides an application of the above-mentioned transparent glass ceramics, and the transparent glass ceramics are used to prepare materials for screen protection covers of consumer electronic products (such as mobile phones, tablets, SLR cameras, smart watches, etc.) and vehicle-mounted display devices.

[0071] The above technical solution provided by the present invention is further explained below through specific embodiments.

[0072] The basic glass in each embodiment is prepared by a casting method, wherein the composition of the basic glass is shown in Table 1:

[0073] Table 1 Chemical composition of base glasses.

[0074]

[0075] The corresponding compounds containing the above oxide components are mixed evenly, melted at 1550-1600°C for 3-5 hours, stirred during the melting process, and then cast in a mold composed of steel bars and steel blocks in a high-temperature molten state at 1450°C to form rectangular glass bricks, and annealed to obtain block-shaped basic glass bricks.

[0076] The basic glass brick is then placed in a precision crystallization furnace (or tunnel kiln) for a heat treatment to obtain glass ceramics, whose XRD is as follows: Figure 1 As shown, the transmittance is Figure 3 As shown, the operating parameters of the temperature and time of the heat treatment are shown in Table 2.

[0077] Table 2 Heat treatment parameters of products.

[0078]

[0079]

[0080] The glass ceramics that have undergone crystallization heat treatment are shaped, cut, and polished to obtain glass ceramic sheets of 50mm*50mm*0.65mm in size, which are then immersed in NaNO3 and KNO3 molten salts for chemical strengthening to obtain chemically strengthened glass ceramics. The specific chemical strengthening process parameters are shown in Table 3.

[0081] Table 3 Secondary strengthening process parameters of products.

[0082]

[0083] The chemically strengthened glass-ceramics were tested for various optical and mechanical indicators, and the method was as follows (the present invention took at least 10 samples of the above size specifications for testing and took the average value): 1. Transmittance test; 2. Haze test; 3. B value test in the color control LAB value; 4. Chemical strengthening property test: CS, DOL; 5. Impact resistance overall drop test; The test results are shown in Table 4:

[0084] Table 4.

[0085]

[0086]

[0087] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A transparent glass ceramic, characterized in that: In terms of mass percentage, the components include: SiO2: 36.0~45.0%, Al2O3: 23.0~32.5%, Na2O: 15.0~22.5%, K2O: 0~1.0%, Li2O: 0.5~5.5%, B2O3: 1.5~8.0%, ZrO2: 1.5~5.5%, TiO2: 0~1.0%, P2O5: 1.0~6.5%, MgO: 0~2.0%, SnO2: 0.1~0.5%; The components also satisfy at least one of the following relationships: 0.98≤(Al2O3%+Na2O%) / SiO2%≤1.36; 18%≤(Na2O+Li2O+K2O)%≤24.50%; 3.0%≤(ZrO2+TiO2+P2O5)%≤9.0%; 2.80%≤(B2O3+MgO)%≤8.0%.

2. The transparent glass ceramic according to claim 1, characterized in that: The transparent glass ceramic also contains 0.1-0.80wt% of a clarifier, wherein the clarifier is selected from one or more of NaCl, Sb2O3, As2O3, nitrates, and sulfates; the sum of the percentages of the components of the transparent glass ceramic containing the clarifier is 100%.

3. The transparent glass ceramic according to claim 1, characterized in that: The main crystal phase of the transparent glass ceramic is a sodium nepheline crystal phase and / or a triclinic nepheline crystal phase, and the secondary crystal phase is one or more of a sodium silicate crystal phase, a β-quartz solid solution crystal phase and a zirconium oxide crystal phase.

4. The transparent glass ceramic according to claim 3, characterized in that: The proportion of the secondary crystalline phase to all crystalline phases is ≤10%, the average grain size is between 20 and 70 nm, and the crystallinity is between 20 and 70%.

5. A method for preparing the transparent glass ceramic according to claim 1, characterized in that: include: Provide basic glass; Heat treating the base glass to obtain the transparent glass ceramic, wherein the heat treatment temperature is 570° C. to 680° C. and the heat treatment time is 15 to 120 min; The base glass comprises SiO2: 36.0-45.0wt%, Al2O3: 23.0-32.5wt%, Na2O: 15.0-22.5wt%, K2O: 0-1.0wt%, Li2O: 0.5-5.5wt%, B2O3: 1.5-8.0wt%, ZrO2: 1.5-5.5wt%, TiO2: 0-1.0wt%, P2O5: 1.0-6.5wt% , MgO: 0~2.0wt%, SnO2: 0.1-0.5wt%; the components also satisfy at least one of the following: 0.98≤(Al2O3%+Na2O%) / SiO2%≤1.36; 18%≤(Na2O+Li2O+K2O)%≤24.50%; 3.0%≤(ZrO2+TiO2+P2O5)%≤9.0%; 2.80%≤(B2O3+MgO)%≤8.0%.

6. The method for preparing the transparent glass ceramic according to claim 5, characterized in that: The preparation method also includes: immersing the transparent ceramic glass in a molten salt to obtain a strengthened transparent glass ceramic; the molten salt temperature is T, 400°C≤T≤480°C; the molten salt is NaNO3 and / or KNO3 in a molten state.

7. The method for preparing the transparent glass ceramic according to claim 6, characterized in that: The depth of the stress layer on the surface of the strengthened transparent glass-ceramic is DOL, 105 μm≤DOL≤155 μm, and the surface compressive stress CS≥650 MPa.

8. The method for preparing the transparent glass ceramic according to claim 6, characterized in that: The Vickers hardness of the surface of the strengthened transparent glass-ceramic is ≥6.5 GPa; when the thickness is less than 0.70 mm and the light wavelength is 400 nm to 780 nm, the average transmittance of the chemically strengthened glass-ceramic product is ≥89%, the color control LAB value is 0.60≤|B|≤1.0, and the haze Haze is ≤0.18%.

9. The method for preparing the transparent glass ceramic according to claim 6, characterized in that: The strengthened transparent glass-ceramic can withstand a height of ≥190 cm and an impact energy of ≥0.35 joule under the condition of 120-grit sandpaper and a 200-g load.

10. A transparent glass-ceramic according to any one of claims 1 to 4 or a transparent glass-ceramic prepared by the preparation method according to any one of claims 5 to 9, used as a material for preparing screen protection covers for consumer electronic products and vehicle-mounted display devices.